Financial cycle controlling in the anti-crisis financial management system of the enterprise - Tkachenko, Volodymyr Valentynovych; Dziadyk, Kh.; Ткаченко, Володимир (Modern Economics, 2020)
The article identifies the need, tasks and tools of controlling in the context of crisis financial management of the enterprise. The priorities of controlling activity in the system of anti-crisis financial management are outlined. The list of urgent tasks of the controlling system in the process of anti-crisis financial management is formed. The issue of controlling the financial cycle of the enterprise has been updated. Scientific views on the interpretation of the concept of "financial cycle" are systematized, their critical analysis and evaluation are carried out. It is proved that control is not a sufficiently developed anti-crisis management system, which is why it needs periodic improvements and implementation, in particular, the development of crisis management and response systems. Controlling in the crisis management system is a system of methods and tools to support management decision-making, planning and control in unstable conditions of the enterprise. The methodical calculation apparatus of calculating the financial cycle of the enterprise is determined. The control map of annual values ​​of the financial cycle. The factor analysis of indicators of a financial cycle of the investigated enterprise is carried out. The expediency of application of economic-mathematical modeling of influence of indicators on a financial cycle of the enterprise for the purpose of development of anti-crisis measures is substantiated. A comprehensive correlation and regression analysis of the impact of indicators on the financial cycle of the enterprise. The results of regression analysis of the impact of indicators on the financial cycle of the enterprise are interpreted and anti-crisis measures.

У статті визначена необхідність, завдання та інструменти контролінгу в умовах антикризового фінансового управління підприємством. Окреслено пріоритети контролінгової діяльності у системі антикризового фінансового управління. Сформовано перелік нагальних завдань системи контролінгу в процесі антикризового фінансового управління. Актуалізовано питання контролінгу фінансового циклу підприємства. Систематизовано наукові погляди на трактування поняття «фінансовий цикл», здійснено їх критичний аналіз та оцінку. Доведено, що контроль не є достатньо розвиненою системою управління антикризовими ситуаціями, саме тому він потребує періодичних удосконалень та впровадження, зокрема, розробки систем попередження та реагування на контроль кризового управління. Контролінг в системі антикризового управління – це система методів та інструментів підтримки прийняття управлінських рішень, планування та контролю в нестабільних умовах діяльності підприємства. Визначено методичний розрахунковий апарат обчислення фінансового циклу підприємства. Побудовано контрольну карту річних значень фінансового циклу на прикладі ПАТ «Львівський міський молочний завод». Проведено факторний аналіз показників фінансового циклу досліджуваного підприємства. Обґрунтовано доцільність застосування економіко-математичного моделювання впливу показників на фінансовий цикл підприємства з метою розробки антикризових заходів. Здійснено комплексний кореляційно-регресійний аналіз впливу показників на фінансовий цикл підприємства. Інтерпретовано результати регресійного аналізу впливу показників на фінансовий цикл підприємства та запропоновано антикризові заходи для ПАТ «Львівський міський молочний завод».
Keywords: controlling; financial controlling; anti-crisis financial management; economic-mathematical modeling; anticrisis program; контролінг; фінансовий контролінг; антикризове фінансове управління; економікоматематичне моделювання; антикризова програма